Risk Factor Analysis of Acute Kidney Injury After Microwave Ablation of Hepatocellular Carcinoma: A Retrospective Study - Yang, Yongfeng; Liu, Fangyi; Yu, Jie; Cheng, Zhigang; Han, Zhiyu; Dou, Jianping; Hu, Jie; Wang, Ze; Gao, Haigang; Yang, Qiao; Tian, Jing; Xu, Yongjie; et al. (Frontiers in Oncology, 2020)
Objectives: Acute kidney injury (AKI) is a recently observed side effect in patients after microwave ablation (MWA) of hepatocellular (HCC) and is associated with negative outcomes. The aim of this study is to explore the risk factors of affecting the occurrence of AKI (stage 1b, 2 and 3), because they have a higher mortality rate than patients with AKI stage 1a and without AKI. Materials and methods: In this retrospective study, a total of 1214 patients with HCC who were treated with MWA under ultrasound (US) guidance in our department between January 2005 and November 2017 were enrolled. We evaluated the influence of 20 risk factors. Univariate and multivariate analysis were used for statistical analysis. The possible risk factors of AKI after MWA for HCC were summarized. RESULTS: The patients with AKI, AKI (stage 1a) and AKI (stage 1b, 2 and 3) after MWA was found in 34, 15 and 19 patients (2.80%, 1.24% and 1.57%), respectively. Among 34 patients with AKI, 10 cases with AKI (stage 1a) and 6 cases with AKI (stage 1b, 2 and 3) recovered before their discharge without any treatment for AKI and 9 cases with AKI (stage 1b, 2 and 3) with further treatment. 4 cases accepted the renal dialysis who had the chronic renal failure before MWA of liver. By univariate analysis, the number of antenna insertions (P=0.027, OR=3.3), MWA time≥20 min (P=0.029, OR=4.3), Creatinine (Cr)-pre above the upper limit of the reference value (P<0.001, OR= 35.5), albumin(Alb)-pre (P=0.030, OR=0.9), and red blood cell (RBC)-pre (P< 0.001, OR= 0.3) were significant risk factors. By multivariate analysis, Cr-pre≥110μmol/L (P<0.001, OR=31.4) and MWA time≥20 min (P=0.043 OR=9.9) were the independent risk factors. CONCLUSION: AKI (stage 1b, 2 and 3) is a relatively serious complication after MWA for HCC, which is related to MWA time and Cr-pre. It requires attention by clinicians. So it is of great necessity to assess Cr-pre level and reduce the MWA time to less than 20min to minimize the risk of AKI after MWA for HCC.